Pointing to an ‘empty’ space: Deixis am Phantasma in face-to-face interaction - Stukenbrock, Anja (Journal of pragmatics, 2014)
This paper is concerned with a key phenomenon in pragmatics: deixis. It starts from a multimodal conceptualization of deixis and argues that based on our interactive practices in demonstratio ad oculos (pointing to visible entities), we likewise accomplish a shared, albeit imagined orientation in cases of Deixis am Phantasma (deixis in the imagination) (Bühler, 1965 [1934]). Based on video recordings from different settings, the paper analyzes in detail the way in which verbal deictics and visible bodily resources work together in shifting the indexical ground or origo away from the participants’ actual space of perception to an imagined space within which the speaker can orient the interlocutors’ attention to physically absent entities. The empirical investigation shows that speakers freely choose between selective deictic displacements along one or two dimensions (place, time, person) and in toto transfers of the origo from the immediate space of perception to an imagined space. The paper proposes that deictic displacements have to be conceived of as operating on a continuum ranging from very subtle origo-shiftings to entire displacements on all dimensions. In face-to-face interaction, they are instantiated both by verbal and kinesic resources and undergo continual metamorphoses in the online construction of talk-in-interaction.